PERAWATAN FIBROUS DYSPLASIA MAKSILA DEXTRA ANTERIOR PADA ANAK USIA 5 TAHUN - Eviwati Sitanggang; Bambang Dwirahardjo; Cahya Yustisia Hasan (Universitas Baiturrahmah, 2015)
Introduction: The Management of Anterior Maxillaris Dextra Fybrous Dysplasia at the 5 years old patient. Fibrous dysplasia is an abnormal bone growth where normal bone is replaced with fibrous connective tissue intermixed with irregular bony trabeculae. It causes bone pain, deformities & pathologic fracture. Fibrous dysplasia is a sporadic benign skeletal disorder that can affect one bone (monostotic) or multiple bone ( polyostotic). Disscusion: The clinical behavior and progression of fibrous dysplasia may also vary, thereby making the management of this condition difficult with few established clinical guidelines. Conclusion: This paper provides a biopsy and reconturing as the choice of treatment.